Occupational Stress, Psychological Distress, and Coping Strategies of First-Level Judges in the Philippines: Examining the Influence of Demographics and Caseloads - Gabayoyo, Lunel J.; Madrigal, Dennis V.; Singson, Deborah Natalia E. (Philippine Social Science Journal, 2024)
Judges worldwide face intense pressure from heavy workloads, emotionally charged cases, and limited resources, leading to burnout and decreased public trust in the justice system. While individual coping is important, systemic change is crucial. This descriptive-correlational study investigated occupational stress, psychological distress, and coping strategies among 357 first-level judges in the Philippines. The study employed three standardized instruments: the Occupational Stress Scale, the Kessler Psychological Distress Scale (K10), and the Filipino Coping Strategies Scale (FCSS). This study revealed that first-level judges in the Philippines experience high levels of occupational stress and psychological distress. However, they also utilize a range of coping strategies to manage these challenges. The study found no significant relationship between occupational stress, psychological distress, and coping strategies and the demographic profile of the first-level judges. This suggests that these challenges are inherent to the judicial role itself rather than influenced by individual differences. The study concludes that interventions and support systems tailored to the specific demands of the profession are needed to address these challenges. The findings served as the basis for the Wellness Program for the first-level court judges in the Philippines.